A study of mechanism on infrared photoresponse in three-dimensional single-walled carbon nanotubes. (October 2016) - Lee, Jongtaek; Park, Taehee; Lee, Jungwoo; Lee, Junyoung; Yang, Jonghee; Ahn, Sang Jung; Yi, Whikun
Abstract: Two fundamental models have been formulated to explain the origin of the photoresponse in the electrical conductivity of SWNT films for an illumination of infrared (IR): the interband transition model (band model) and the bolometric model. However, the photoresponse of SWNTs has generated considerable debate, with various studies leading to different interpretations of the origin of photoconductivity. We fabricated three-dimensional SWNTs (3D-SWNTs) suspended between SiO2 pillars grown on flat quartz to suggest the origin of the photoresponse of SWNTs. From the measurements of photoconductivity of our samples under three conditions using a continuous Xe lamp, one IR laser pulse, and a repeated IR laser pulse, we demonstrated that two response modes coexist.